DISTRIBUIÇÃO E PARTIÇÃO GEOQUÍMICA DE METAIS EM SEDIMENTOS DE ESTUÁRIOS DE MACROMARÉ, MARANHÃO, BRASIL. - SANTOS, Thays Thayanne Luz (2018)
The present study evaluated the distribution and geochemical partitioning of trace metals in the estuarine sediments of the São Marcos Bay (BSM) and the Anil River Estuary (ERA) according to the different uses of the basins adjacent to these estuaries. Sampling campaigns were carried out in the dry season of 2016. It was two in BSM (August and December) and in the ERA (October and December). Throughout each environment were determined 6 sample points, totaling 12 sites. Physical-chemical parameters such as temperature, salinity, pH, dissolved oxygen and suspended particulate matter were determined on the subsurface of the water column. With the aid of the Gibbs dredger two launches per point for the collection of the surface sediments in places permanently covered by the water were made. The determination of the grain size,% of organic matter (OM) and calcium carbonate (CaCO3) and, of metals, in two size fractions (Fe, Al, Mn, Cu, Pb, Cr, Zn and Ni) were performed. All analyzes used duplicate samples. The result of the grain size analysis showed the predominance of sand (> 92 %). The comparison of the results obtained in the grain size fraction < 2 mm and <63 μm showed that the second fraction allows better geochemical interpretation to identify the different origins of the evaluated metals. At BSM, the sediment showed an upstream grain size increase in both campaigns. The sediment in the ERA showed a decrease in the grain size throughout the environment. The percentages of MO and CaCO3 were higher in the ERA. The factors of enrichment of metals evidenced the greater environmental contamination of the ERA, in relation to BSM (grain size fraction < 2 mm). The significant statistical correlation of the metals in the ERA with OM, which has the potential to make metals bioavailable, should be the major concern for environmental monitoring and management of the area. However, significant enrichment of Mn, Pb and Cr, Al and Fe was observed in a certain region of the estuary near to the port activities. Therefore, the sediments of both environments present metal anomalies, with geochemical partitioning related to materials that can be removed as OM and carbonates, pointing out the need for environmental monitoring and management of these estuaries.